C-reactive protein deficiency ameliorates experimental abdominal aortic aneurysms - Fu, Yu; Liu, Haole; Li, Kexin; Wei, Panpan; Alam, Naqash; Deng, Jie; Li, Meng; Wu, Haibin; He, Xue; Hou, Haiwen; Xia, Congcong; Wang, Rong; et al. (Frontiers in Immunology, 2023)
Background: C-reactive protein (CRP) levels are elevated in patients with abdominal aortic aneurysms (AAA). However, it has not been investigated whether CRP contributes to AAA pathogenesis.Methods: CRP deficient and wild type (WT) male mice were subjected to AAA induction via transient intra-aortic infusion of porcine pancreatic elastase.AAAs were monitored by in situ measurements of maximal infrarenal aortic external diameters immediately prior to and 14 days following elastase infusion.AAA pathologies were assessed by histochemical and immunohistochemical staining procedures. The influence of CRP deficiency on macrophage activation was evaluated in peritoneal macrophages in vitro. Results: CRP protein levels were higher in aneurysmal than that in nonaneurysmal aortas. Aneurysmal aortic dilation was markedly suppressed in CRP deficient (aortic diameter: 1.08 ± 0.11 mm) as compared to WT (1.21 ± 0.08 mm) mice on day 14 after elastase infusion. More medial elastin was retained in CRP deficient than in WT elastase-infused mice. Macrophage accumulation was significantly less in aneurysmal aorta from CRP deficient than that from WT mice. Matrix metalloproteinase 2 expression was also attenuated in CRP deficient as compared to WT aneurysmal aortas. CRP deficiency had no recognizable influence on medial smooth muscle loss, lymphocyte accumulation, aneurysmal angiogenesis, and matrix metalloproteinase 9 expression. In in vitro assays, mRNA levels for tumor necrosis factor α and cyclooxygenase 2 were reduced in lipopolysaccharide activated peritoneal macrophages from CRP deficient as compared to wild type mice. Conclusion: CRP deficiency suppressed experimental AAAs by attenuating aneurysmal elastin destruction, macrophage accumulation and matrix metalloproteinase 2 expression.